Contributions of animal models to the study of mood disorders - Samira S. Valvassori; Josiane Budni; Roger B. Varela; Joao Quevedo (Brazilian Journal of Psychiatry, 2013)
Mood disorders are a leading cause of morbidity and mortality, yet their underlying pathophysiology remains unclear. Animal models serve as a powerful tool for investigating the neurobiological mechanisms underlying psychiatric disorders; however, no animal model developed to date can fully mimic the “corresponding” human psychiatric disorder. In this scenario, the development of different animal models contributes to our understanding of the neurobiology of these disorders and provides the possibility of preclinical pharmacologic screening. The present review seeks to provide a comprehensive overview of traditional and recent animal models, recapitulating different features and the possible pathologic mechanisms of mood disorders emulated by these models.